Shot noise of low energy electron field emission due to Klein tunneling - Sun, Sheng (2013)
This paper investigates the property of shot noise for low energy electron field emission from a single-layer vertically aligned graphene sheet assuming the emission process is due to Klein tunneling. In our model, we use two different methods (relativistic WKB and transfer matrix) to calculate the transmission coefficient and thus obtain the Fano factor (γ or suppression of shot noise) as a function of temperature T, Fermi energy Ef, and local electric field F. It is found that a universal maximum value of about γ = 1/3 can be reached at low temperature limit within a certain range of local electric field.